1984
DOI: 10.1111/j.1365-2842.1984.tb00575.x
|View full text |Cite
|
Sign up to set email alerts
|

The fracture toughness of tooth coloured restorative materials

Abstract: A fracture mechanics approach has been used to quantify the failure of tooth coloured restorative materials which are subjected to tensile forces. The materials examined included silicates, glass ionomers, composites (both chemically and photo-initiated) and bonding resins for composites. The parameter chosen was the plane strain critical stress intensification factor, KIC. Silicate and glass ionomer are both brittle and have values for KIC inferior to those of composites. Composites have fracture toughnesses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0
3

Year Published

1987
1987
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(32 citation statements)
references
References 23 publications
0
29
0
3
Order By: Relevance
“…Cracks in dental composites with good filler/ matrix adhesion generally propagate through the resin matrix. 30,31 Therefore, any factor that enhances the strength and fracture resistance of the matrix, for example, enhancing the cure of the polymer, should enhance the fracture toughness of the composite. Likewise, anything that softens the polymer matrix and facilitates crack propagation, such as uptake of a solvent, should reduce fracture toughness.…”
Section: Discussionmentioning
confidence: 99%
“…Cracks in dental composites with good filler/ matrix adhesion generally propagate through the resin matrix. 30,31 Therefore, any factor that enhances the strength and fracture resistance of the matrix, for example, enhancing the cure of the polymer, should enhance the fracture toughness of the composite. Likewise, anything that softens the polymer matrix and facilitates crack propagation, such as uptake of a solvent, should reduce fracture toughness.…”
Section: Discussionmentioning
confidence: 99%
“…Fracture toughness (K IC ) is an intrinsic material property, independent of specimen dimensions, that represents a material's resistance to crack propagation [13] and has been employed to test resin-bonded composites (RBCs) [14][15][16][17][18][19][20][21][22][23][24][25][26], GIs [18][19][20]24,25,[27][28][29][30][31][32], ceramics [33][34][35] and dental amalgams [20,24,25,36,37]. The aim of the current study was to investigate whether the single-edge notched (SEN) bend test-piece K IC testing protocol is a reproducible and discriminatory testing methodology to act as a performance indicator for encapsulated and hand-mixed GI restorative materials.…”
Section: Introductionmentioning
confidence: 99%
“…When present, these voids may cause drawbacks within a restoration such as 10) : marginal leakage and discolouration, increased wear due to the stress concentration around voids, decreased fl exural strength and also incomplete adhesion between the resin-composite and dentine 11) . There have been several attempts to solve the problems associated with direct composite restorations, including increasing the percentage of fi ller content in the composite matrix and reducing the size of fi ller particles [12][13][14] . Several studies showed that heavier fi ller loading would result in increase in fracture toughness of the material 15) , while others concluded that fi ller content has no role in fracture behaviour 16) .…”
Section: Introductionmentioning
confidence: 99%